Ultrasound processing of guava juice: Effect on structure, physical properties and lycopene in vitro accessibility - Campoli S.S. (2018)
The authors are grateful to the São Paulo Research Foundation (FAPESP, Brazil) for funding the projects n° 2016/18052-5, 2015/15507-9, and 2014/16998-3; to the National Council for Scientific and Technological Development (CNPq, Brazil) for funding the project n° 401004/2014-7, the productivity grant of P.E.D. Augusto (306557/2017-7) and the M.Sc. scholarship of SS Campoli; and to Cienciactiva for the M.L. Rojas Ph.D. scholarship (CONCYTEC, Peru; Contract 087-2016-FONDECYT), from the ‘‘Consejo Nacional de Ciencia, Tecnología e Innovación Tecnológica“.